PENGARUH PARITAS DAN INDEKS MASA TUBUH (IMT) TERHADAP KEJADIAN PREEKLAMSI DI KABUPATEN BANYUMAS - Fajarsari, Dyah; Prabandari, Fitria (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
Preeclampsia and eclampsia is the unity of disease directly caused by pregnancy. The disease is characterized by hypertension, proteinuria and edema as well as the worst conditions ie convulsions or coma. High blood pressure in pregnant women impacts vary. Maternity rate in Banyumas reached 118 cases per 100 thousand live births and is ranked third in the province of Central Java, or as many as 33 cases. From some cause eklamasi and bleeding into a sizeable contributor figures are respectively 14 and 5 cases. Objective research is to analyze the effect of parity and body mass index (BMI) on the incidence of preeclampsia in Banyumas. This type of research is analytic survey with a retrospective case control approach. The population in this study were pregnant women with pre-eclampsia in five health centers with the highest number of pre eclampsia in Banyumas in the year 2015. The sample in this study using the technique of accidental sampling of 60 pregnant women who are diagnosed preeklampsi as the case group and 60 respondents mothers normal pregnant and data analysis using Chi Square. Research results obtained are in primigravida pregnant women who develop preeclampsia as many as 43 people (71.7%), pregnant women with a BMI> 29 who develop preeclampsia as many as 39 people (65.0%). Conclusion: there is an influence on the incidence of preeclampsia parity with p <0.000; there is the effect of BMI on the incidence of preeclampsia with a p-value of <0.000. Keywords: parity, body mass index (BMI), Preeclampsia